Avstro-Ogrska monarhija v besedi in podobi - Slovenci II. Kranjska, Primorje - Slavec Gradišnik, Ingrid; Kropej Telban, Monika (ZRC SAZU, Založba ZRC, 2018)
Two years after the first book "Austro-Hungarian Monarchy in Word and Image: Slovenes 1, Styria, Porabje and Prekmurje, Carinthia" (2016) has been published, is now out also the second book: "Austro-Hungarian Monarchy in Word and Image: Slovenes 2", presenting Kranjska (Carniola) and Primorje (Coastal region). Both books make the whole picture of Slovenes as included in the monumental book series "Die österreichisch-ungarische Monarchie in Wort und Bild" which was projected by the archeduke Rudolf and was published between 1884-1902. Translated are the chapters which discuss life, culture and economy of Slovenes living in Austro-Hungarian monarchy. Prevailing are the ethnographical descriptions of the regions, the presentation of inhabitants and their position in the context of the Austro-Hungarian monarchy and other countries of that time. The authors are of different profiles and interests, and their studies are important sources for Slovenian culture and economy which was up till now too often overlooked.